Analisis Instagram terhadap Gaya Hidup dan Pola Komunikasi pada Remaja Karang Taruna Cempaka Putih, Kecamatan Gondangrejo, Karanganyar - Yuliana, Margaretha Evi; Arini , Dhefilyn Wahyu Widia; Renjani, Inenimas Arya (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The advancement of information and communication technology, particularly through social media platforms like Instagram, has a significant influence in shaping the lifestyle and communication patterns of teenagers. This study aims to analyze how teenagers in the Karang Taruna Cempaka Putih youth organization in Gondangrejo District, Karanganyar, use Instagram as a medium for self-expression to showcase their lifestyle and create new dynamics in interaction and communication in this digital era. With the development of social media, Instagram has become not only a platform for sharing photos and videos but also a space for teenagers to build their identity, explore creativity, and connect with their social environment. A descriptive qualitative method was selected as the research method for this study by observing Instagram accounts of seven 22-year-old teenagers. Data were collected through screenshots of Instagram Stories, feeds, reels, and comments, capturing activities such as vacations, nature adventures, cafe visits, significant celebrations, and participation in campus organizations. This demonstrates that social media has become a space for teenagers to express themselves. Communication patterns on Instagram are reflected in creative captions and interactive comments, creating a relaxed and dynamic atmosphere. These patterns show that Instagram is an effective medium for building communication styles. The implications of this study include an increased understanding of socio-cultural dynamics, the influence of social media on identity formation, and the development of communication skills.